Analisis penerimaan retribusi dan strategi pengembangan objek wisata Taman Anggrek Sri Soedewi Provinsi Jambi - Aghniyah Aghniyah; Syaparuddin Syaparuddin; Erni Achmad (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2020)
study aims to analyze retribution income of Taman Anggrek Sri Soedewi object and expected to produce a possible strategy that can be applied to increase the amount of retribution income in the tourism department of Anggrek Sri Soedewi Garden object in Jambi Province. In this research, used are is primary and secondary of data. This study usds data from the financial statements of tourism within 4 years from 2014 to 2018. The data were collected by questionnaire, observation, interview conducted to 21 respondents comprising of head division, and managements of tourism object, as well as visitors was selected by accidental sampling method. In SWOT matrix analysis, results obtained six alternative strategies, namely : (1) enhancement cooperation, (2) improving development program, (3) improving facilities and infrastructure, (4) allocation of human resources, (5) increasing a flower collection, and (6) increased promotion.